The construction of neurogenesis-related ceRNA network of ischemic stroke treated by oxymatrine. Issue 15 (7th September 2022) - Zhang, Xiaoling; Yao, Wentao; Zhao, Wannian; Sun, Yingru; Wu, Zongkai; He, Weiliang; Ji, Yingxiao; Gao, Yaran; Niu, Xiaoli; Li, Litao; Wang, Hebo
Abstract : Background: Known as a disease associated with high mortality, disability and a significant financial burden, ischemic stroke ranks as one of the three diseases threatening human health. Recent advances in omics technology created opportunities to uncover the mechanism in ischemic stroke occurrence and treatment. In this study, we aimed to construct the competitive endogenous RNA (ceRNA) networks of ischemic stroke treated by oxymatrine intervention. Method: The middle cerebral artery occlusion (MCAO) mouse model of ischemic stroke was constructed, and oxymatrine was administered. Then RNA-Sequencing was performed and integrated analysis of mRNAs, lncRNAs and circRNAs was conducted to reveal the pharmacology of oxymatrine. Functional enrichment analysis was performed to explore the underlying mechanism of differentially expressed (DE) mRNAs. The protein-protein interaction (PPI) network of neurogenesis-related genes and long noncoding RNAs (lncRNAs)/circular RNAs (circRNAs) based ceRNA networks were constructed. Results: First, this study revealed the DE-mRNAs, DE-lncRNAs and DE-circRNAs between Oxymatrine treated group and the MCAO group. Then, the common 1231 DE-mRNAs, 32 DE-lncRNAs and 31 DE-circRNAs with opposite trends were identified. The Kyoto Encyclopedia of Genes and Genomes to identify the functional enrichment of 1231 DE-mRNAs were enriched in neurogenesis-related biological processes. Based on neurogenesis-related DE-mRNAs, the PPI network was constructed, and hub genes were identified based on centrality. Finally, both the lncRNA-based and circRNAs-based ceRNA networks were constructed. Conclusion: In summary, this study identified novel coding and noncoding ischemic stroke targets of oxymatrine-treated MCAO. Most importantly, we identified lncRNAs and circRNAs candidates as potential oxymatrine targets and constructed the neurogenesis-related ceRNA networks.